Echocardiographic evaluation of aortic elasticity parameters in aortic stenosis patients with preserved ejection fractions undergoing transcatheter aortic valve implantation (Annals of Medical Research, 2022)
Aim: Aortic stiffness is an important risk factor that reflects the mechanical tension and elasticity of the aorta and predicts cardiovascular mortality and morbidity. However, it has been found that aortic stiffness contributes to both symptom burden and clinical outcomes in patients with aortic stenosis (AS). In our study, we aimed to evaluate the effect of transcatheter aortic valve implantation (TAVI) on aortic elasticity parameters by echocardiography in patients with severe aortic stenosis, especially with preserved ejection fraction.Materials and Methods: A total of 55 consecutive patients with symptomatic severe AS who underwent TAVI were included in the study. Demographic data, echocardiographic and aortic elasticity measurements of all patients were measured before and 6 months after the procedure. To evaluate the elastic properties of the aorta, aortic strain, distensibility and stiffness index were calculated.Results: Left ventricular mass index (LVMI) (p
Keywords: Aortic stenosis; Transcatheter aortic valve implantation; TAVI; Aortic stiffness; Aortic distensibility; Left ventricular mass index